Pendidikan Kesehatan tentang Resusitasi Jantung Paru pada Petugas Kesehatan di Puskesmas Tondano - Irnawati Irnawati; Zahrah Maulidia Septimar; Fatoni Fatoni; Abul A’la Al Maududi; Wahyu Ridwan Nugroho (PELITA NUSA TENGGARA, 2026)
Cardiac arrest is one of the leading causes of death from cardiovascular disease and requires immediate management through high-quality cardiopulmonary resuscitation (CPR) to improve patient survival. Primary healthcare workers at community health centers play a crucial role as frontline providers in delivering the initial response to cardiac arrest cases. However, healthcare workers' knowledge and preparedness regarding CPR algorithms may decline over time without regular training and refresher programs. This community service program aimed to improve healthcare workers' knowledge of cardiopulmonary resuscitation through a health education intervention at Tondano Community Health Center. The program employed a one-group pretest–posttest design involving 31 healthcare workers. The intervention consisted of a pretest, interactive lectures, CPR demonstrations based on the 2020 American Heart Association (AHA) Guidelines, group discussions, and a posttest evaluation. Data were analyzed descriptively, followed by the Wilcoxon Signed-Rank Test. The results showed that the mean knowledge score increased from 39.35 ± 18.28 before the intervention to 54.84 ± 19.19 after the intervention, representing a mean improvement of 15.48 points. Statistical analysis demonstrated a significant difference between the pretest and posttest scores (p < 0.001). Health education was effective in improving healthcare workers' knowledge of cardiopulmonary resuscitation. Therefore, similar educational programs should be conducted regularly as part of continuing professional development to strengthen the emergency response competencies of healthcare workers in primary healthcare facilities.